Synthesis of novel polyhydroxylated pyrrolidine–triazole/-isoxazole hybrid molecules. Issue 7 (19th December 2014) - Lin, Cheng-Kun; Cheng, Li-Wei; Li, Huang-Yi; Yun, Wen-Yi; Cheng, Wei-Chieh
Abstract : A straightforward synthesis of novel, 2-heterocyclyl polyhydroxylated pyrrolidines is described. Abstract : A straightforward synthesis of novel, 2-heterocyclyl polyhydroxylated pyrrolidines is described. Stereocontrolled additions of nucleophiles to cyclic nitrones generated the corresponding 2, 3- trans adducts, allowing the synthesis of the corresponding pyrrolidines via key intermediates bearing an alkyne and a nitrile oxide. Three hybrid systems, including a pyrrolidine with two isoxazoles and one triazole, are efficiently prepared via 1, 3-dipolar cycloaddition. Biological testing of the product alkaloids showed that subtle structural variations have drastic effects on their inhibitory activities against glucosidases.